Rapid Detection of Aspergillus fumigatus Using Multiple Cross Displacement Amplification Combined With Nanoparticles-Based Lateral Flow - Jiang, Luxi; Li, Xiaomeng; Gu, Rumeng; Mu, Deguang (Frontiers in Cellular and Infection Microbiology, 2021)
Aspergillus fumigatus is an opportunistic, ubiquitous, saprophytic mould which can cause infection in the lungs, nose, eyes, brain, and bones in humans, especially in immunocompromised patients. However, it is difficult to diagnose Aspergillus fumigatus infection quickly. Here, we introduce a new detection method, namely multiple cross displacement amplification (MCDA) combined with nanoparticle-based lateral flow biosensor (LFB) (MCDA-LFB), which can detect Aspergillus fumigatus very well. A set of 10 primers was designed specifically to recognize 10 different regions of the Aspergillus fumigatus-specific gene annexin ANXC4. The best MCDA condition is 66℃ for 35 minutes. The minimum concentration that can be detected by this method was 10fg. We found that the whole process could be controlled within 60 minutes including the preparation of DNA (20 min), MCDA reaction (35 min) and results reporting (2min). These results show that this assay is suitable for the rapid, sensitive and specific detection of Aspergillus fumigatus in clinical samples.